ANTIOXIDANT ACTIVITY OF HYDROALCOHOLIC EXTRACT OF GREEN GEDI LEAVES (Abelmoschus manihot L.) USING CUPRAC (CUPRIC ION REDUCING ANTIOXIDANT CAPACITY) METHOD - Kaban, Vera Estefania; Nasri, Nasri; Suci, Nurul; Lubis, Muhammad Fauzan; Rani, Zulmai; Nasution, Haris Munandar (Talenta Publisher, 2025)
Free radicals induce oxidative stress, which plays a pivotal role in the pathogenesis of various degenerative diseases. Abelmoschus manihot L., locally known as green gedi, is recognized for its rich secondary metabolite content with potential antioxidant properties. This study aimed to evaluate the antioxidant activity of the hydroalcoholic extract of green gedi leaves using the Cupric Ion Reducing Antioxidant Capacity (CUPRAC) method. Extraction was conducted via maceration using a 90% hydroalcoholic solvent, followed by comprehensive phytochemical screening and simplicia characterization. The antioxidant capacity was quantified by determining the IC50 value through linear regression analysis of inhibition percentage versus concentration. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, glycosides, saponins, tannins, and triterpenoids/steroids. The hydroalcoholic extract exhibited